Contribution in the Study of Aujeszky’s disease. I. Gross and Histological changes in the liver of piglets - ΣΤΟΦΟΡΟΣ Ε.; ΠΑΠΑΔΟΠΟΥΛΟΣ Χ.; ΜΑΣΤΡΟΠΑΝΝΗ -ΚΟΡΚΟΛΟΠΟΥΛΟΥ Μ.; ΑΞΙΩΤΗΣ Ι.; ΠΑΠΑΝΤΩΝΑΚΗΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The gross and histological changes were studied in liver of pig naturally infected with the Aujeszky’s disease. We detected small necrotic focies, scattered throughout the liver parenchyma, which corresponded histologically with intralobularor or perilobular areas of coagulative necrosis. In all the examined sections inclusion bodies were not found in the necrotic cells. The Authors think that the gross lesions - focals necrosis - which were found on the diaphragmatic surface of the liver are pathognomonic of the disease.